Effectiveness PBL Model on Mathematical Problem Solving Ability - Yusnita Amelia Yusnita Amelia; Indah Kumalasari Indah Kumalasari; Putri Kurniawati Putri Kurniawati; Fitriyah Amaliyah Fitriyah Amaliyah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
One of the learning models that can develop ability breakdown problem mathematical is a learning model based on problem or Problem Based Learning (PBL). Study This aiming For see effectiveness of learning models based on problem (PBL) against ability breakdown problem students' mathematics in elementary school. Research This use method quantitative with type pre-experimental research with design one-shot case study involving One class student class 4 consisting of of 20 students at SDN 3/4 Margoyoso . Instruments used is test ability breakdown problem mathematical . Data analysis using one sample test . Based on criteria rejection hypothesis zero (H 0 ), result study show Sig. value ( 2-tailed ) is 0.101, more big from 0.05. This is means ability mathematical student reach Criteria Completion of Learning Objectives (KKTP ) 75. With implications from research , namely improvement participation students , implementation the right concept in life real , and success the role of teachers as supportive faciliator student in the learning process.